Formação continuada e o PIBID: uma análise à luz do ciclo de políticas dos/as professores/as supervisores/as da educação básica do subprojeto de Educação Física da Universidade Federal do Maranhão - SANTOS, Antonio Higor Gusmão dos (2023)
The dissertation is linked to the research group “Policies, Educational Management and Human Formation” and the line “History, Educational Policies and Human Formation” of the Graduate Program in Education (PPGE) of the Federal University of Maranhão (UFMA). Its theme is the Educational Policy for Teacher Training, especially the Institutional Scholarship Program for Initiation to Teaching (PIBID) and the Continuing Training of Basic Education Teachers. The PIBID began in 2007 and although the program focuses on the initiation to teaching and initial training, this research has the general objective of analyzing the actions developed within the scope of the Physical Education subproject/PIBID/UFMA if have contributed as a continuing education for supervisor teachers of basic education, and as specific objectives: a) Understand the policies of initial and continuing education for the training of teachers of basic education; b) Analyze the official documents of PIBID and the institutional project of UFMA, in order to recognize in the context of the influence and production of the text actions of the program as a space for continuing education; and c) To analyze how the actions developed in the context of the practice by the Physical Education/PIBID/UFMA subproject made possible a continuous formation of the supervisors teachers. We use a qualitative approach in a descriptive and analytical way, using official documents such as laws, decrees, public notices, ordinances, projects and reports that deal with the national policy of Teacher Training, giving priority to those of Continuing Education, on the PIBID in scope nationally and in the context of UFMA and its Physical Education subproject. In addition, questionnaires and semi- structured interviews were carried out with the five supervisors. As an epistemological focus, we chose to work with the Policy Cycle based on authors such as Ball (2011) and Mainardes (2006, 2011, 2013), to understand the influences of groups in the constitution of PIBID, to understand the consents on the production of the text of this program and how it acted in the context of the Physical Education subproject at UFMA. Our discussions were discussed with authors such as Bourdieu (2004, 2014, 2017), Imbernón (2011), Santos E. (2014) and Tardif (2014). The analyzes showed that laws and programs are changing as a result of changes in governments, groups of politicians who exert pressure, people linked to economic sectors and social groups that influence policy since its conception, in the production of its text, even in the context of their practice. We found that there are elements in the laws that regulate Teacher Training, which enable an articulation between initial and continuing training. However, in PIBID, this articulation was not thought of at the national level, but in the local context of UFMA and the Physical Education Subproject, we found that there were actions that contributed to the Continuing Education of supervisors, through collaborative training, studies that enabled the reflection of their practice among other actions. Therefore, it is up to the PIBID to rethink how to create opportunities for these trainings not to happen only in a specific subproject, but that in all of them there can be this Continuing Training for the teachers of basic education who act as supervisors of the PIBID.